A construção dos processos identitários no ensino on-line: efeitos de sentido e representações - Lemos, Rosana Emílio (2011)
The on-line teaching is characterized by a model through distance via digital nets, in which the learner conects himself to a virtual platform and there finds materials, tutory and other learners to learn with different ways of organization: ready subjects, cooperated activities, this way, the on-line teaching focus itsef in the development of an active and shared learning. In this cenary, it is found the social nets that offer language courses or put itself as spaces of support to a cooperated learning. The blog named English Experts, has as goal “to help English students with daily hints” (BRANDÃO, 2010), how they can read in their own description. The blog was created in 2006 by Alessandro Brandão, that introduces himself just as an English student who wants to help other students (English made by learners for learners! by Brandão), and configures itself as an anlysis corpus of this search. What is more interesting in the blog it is to observe how this English on-line learning discursive and interaction process happens and, how this interaction builds identities and representations of the cooperated teaching of English. This way, from the analysis of the blog and from some e-texts, the current search has as a general goal to reflect about the on-line teaching of a foreign language – English – in social nets. The specific goals are: a) to check how the discursive and identitaries of the English language teaching happen in the blog and how they build conceptions of the language and vigents teaching in this virtual environment in which the teachers and the students are not well established; b) to observe what discursive representations of the English teaching are build. So the discursive perspective chooses the theoric basis that are used, such as the notions already consolided by Foucault of discursive practices, speech and identity and these are linked to reflections about the teaching of a second language on the net, relating them to the notions of subject and language, chosen by new technologies, in special those that are present in the cybermidia. The representation of English teaching in the blog is based on speech that does not learn English in a formal way, with courses, but in a daily practice, in contact with the language of “natural” way. Thus, learning English should be collaborative and interative, you learn because you want to learn, and when you want to search, to seek out and interact, so if you have the interaction, exchange of knowledge. For both, it creates the identity of the moderator and developer of English teaching by replacing the figure of an English teacher in traditional learning.